Nonlinear Control Method of Photovoltaic Power Generation LVRT Based on Adaptive Maximum Power Tracking - Yin, Jun; Nie, Haoyu; Huang, Xiaobo; Xu, Guojie; Xu, Jing; Liu, Yuhan (Frontiers in Energy Research, 2022)
With the continuous increase in the scale of photovoltaic grid connection, the impact of the safe and stable operation of photovoltaic power generation systems on the grid cannot be ignored. When a short-term failure of the power grid occurs, the large-scale disconnection of the unit will seriously affect the stability of the grid voltage and frequency. Therefore, this paper proposes a non-linear control method for photovoltaic power generation low voltage ride through (LVRT) based on adaptive maximum power tracking. This method adaptively adjusts the power tracking trajectory through the feedforward control of the voltage drop amplitude. Cooperating with the nonlinear control of the grid-connected inverter, this method can quickly and effectively control the power output of photovoltaic cells on the basis of providing appropriate reactive power support, so as to realize the rapid response of grid system. Through the simulation in PSCAD, it is verified that the control method described in this article can well realize the LVRT in different amplitudes of the photovoltaic system, especially when zero voltage drops occur.